Touch anticipation mediates cross-modal Hebbian plasticity in the primary somatosensory cortex. (May 2020) - Maddaluno, Ottavia; Guidali, Giacomo; Zazio, Agnese; Miniussi, Carlo; Bolognini, Nadia
Abstract: Paired associative stimulation (PAS) protocols can be used to induce Hebbian plasticity in the human brain. A modified, cross-modal version, of the PAS (cross-modal PAS, cm-PAS) has been recently developed. The cm-PAS consists in the repetitive pairings of a transcranial magnetic stimulation (TMS) pulse over the primary somatosensory cortex (S1) and a visual stimulus depicting a hand being touched; a 20 ms of inter-stimulus interval (ISI) is required to affect S1 plasticity, in turn modulating tactile acuity and somatosensory evoked potentials. The present study explores the role of anticipatory simulation in the cm-PAS efficacy, which could be responsible for such a short ISI. To this aim, we compared the effect of the original, fixed-frequency, cm-PAS to that of a jittered version, in which the time interval between trials was not steady but jittered, hence avoiding the anticipation of the upcoming visual-touch stimulus. Moreover, in the jittered PAS, the ISI between the paired stimulations was varied: it could match the early, somatosensory-driven, activation of S1 (20 ms), or the mirror recruitment of S1 by touch observation (150 ms). Results showed that tactile acuity is enhanced by the fixed-frequency cm-PAS, with an ISI of 20 ms between paired stimulation (visual-touch stimulus and TMS pulse over S1), and also by the jittered cm-PAS but only if the ISI is of 150 ms. These findings suggest that the cm-PAS with a jittered frequency, by preventing an anticipatory pre-activation of S1, delays the timing of the interaction between the visual-touch stimulus and the cortical pulse. On a broader perspective, our study highlights the possible involvement of sensory anticipation, likely through mirror-like simulation mechanisms, in tactile mirroring, as well as its influence of the optimal interval between the afferent and the magnetic pulse during PAS protocols.